Pediatric cutaneous tuberculosis: Indian scenario - Bhushan Kumar; Sheetanshu Kumar (Wolters Kluwer Medknow Publications, 2018)
Burden of tuberculosis still persists in developing countries despite major advances in its treatment strategies. Cutaneous tuberculosis which is a form of extra-pulmonary tuberculosis is seen in a small but significant subset of patients visiting dermatology outpatient services. Cutaneous tuberculosis is characterized by a spectrum of multiple distinct clinical and histopathology presentations. A significant proportion of patients with cutaneous tuberculosis are seen in paediatric age group. Clinical features in children remain mostly the same as that in adults with cutaneous tuberculosis. However, systemic and lymph node involvement and incidence of disseminated disease is observed more commonly in paediatric age group . Awareness among clinicians of the clinical manifestations of cutaneous tuberculosis is of paramount importance for early diagnosis and management of cases with paediatric cutaneous tuberculosis. This would significantly prevent morbidity and complications of the disease . This review aims to discuss the epidemiology, clinical and histopathological features, diagnosis, differential diagnosis and treatment options in children with tuberculosis, especially in the Indian context.